Intuitive anger in the context of crime and punishment - Côté-Lussier, Carolyn (Psychology, crime & law, 2023)
Anger is a key emotion in terms of understanding public responses toward crime: it is frequently mobilized in public discourses and is elicited by specific incidents. This study focuses on intuitive anger: a rapidly emerging negative emotional response that eschews principles of punishment but nevertheless contributes to punitiveness. This study uses facial electromyography to measure intuitive anger, and assess its effect on punitiveness drawing on data collected among university students in Canada (N = 87). The study’s repeated-measures experimental design allows for testing the hypotheses that: (i) individuals will experience greater intuitive angry responses when making punitive decisions for purported ‘stereotypical criminals’ and that (ii) anger will appear early in the decision-making process, and lead to more punitive decisions. The results of crossed-multilevel regression models provide evidence of the manifestation of anger within half of a second of individuals’ engagement in punitive decision-making. Intuitive anger follows principles that are central to intergroup relations, although it was not found to be predictive of rapid punitive decisions. The findings are discussed in terms of the moral and social implications of intuitive anger in the context of punitiveness toward crime.